Effects of Additional Polyvinyl Alcohol (PVA) on the Physiochemical Properties of Chitosan-Glutaraldehyde-Gelatine Bioplastic - Muh Jufri; Retno Ariadi Lusiana; Nor Basid Adiwibawa Prasetya (Jurnal Kimia Sains dan Aplikasi, 2022)
This study investigated the effects of additional PVA on the physicochemical properties of the chitosan-glutaraldehyde/gelatin bioplastic composite. The best results of the bioplastic film were obtained at a concentration of 3% PVA, with a tensile strength value of 3.3 MPa, flexibility reached 54%, a thickness value of 0.24 mm, percentage of inhibition against E. coli and S. aureus was 21.8% and 8.8% respectively. The FTIR spectrum results showed no change in the wavenumber of the chitosan and gelatin chitosan spectrum with OH, CO, and NH functional groups. The spectrum indicates that only physical interactions occurred. The bioplastics are similar in thermal stability and have slight differences in bioplastic morphological contours. The average thickness of the bioplastics is between 0.20–0.26 mm. Based on the Japanese Industrial Standard (JIS), all bioplastics meet the standard thickness, which is < 0.25 mm, excluding chitosan, which has a thickness of 0.26 mm. The addition of PVA into the bioplastics structure increased the hydrophobicity, pH resistance, and flexibility of bioplastics. Meanwhile, additional PVA decreased biodegradability, only degraded by 60% at eight weeks. Based on these data, not all bioplastics can meet the degradation time criteria set by the international bioplastic standard ASTM D-6002, that bioplastics must be 100% degraded within eight weeks. Bioplastics made from chitosan and chitosan-gelatin have been degraded by 90% for 48 weeks. Based on the antibacterial properties, the inclusion of PVA into the bioplastic structure enhances the antibacterial properties.